"When there's collective leadership, there's the power to make changes": A realist evaluation of a collective leadership intervention (Co-Lead) in healthcare teams. (May 2023) - De Brún, A.; McAuliffe, E.
There is accumulating evidence for collective approaches to leadership, where multiple individuals share leadership roles, but there remains a lack of theory-informed research on how collective leadership is fostered in practice. This study evaluated the impact of a collective leadership intervention, exploring what works for whom, how, and under what circumstances through a mixed-methods realist evaluation of four case studies. Eight context-mechanism-outcome configurations (theories) were extrapolated that elucidate the mechanisms triggered to drive outcomes in particular settings. This is the first study to apply a realist lens to understand collective leadership and articulate the generative mechanisms that enable/inhibit collective leadership in healthcare teams.